The economic consequences of obesity and overweight among adults in Quebec - Blouin, Chantal (Can J Public Health, 2016)
OBJECTIVES: This article presents the first study of the economic consequences of obesity and overweight in the Canadian province of Quebec. The article examines three types of direct costs: hospitalizations, medical visits and drug consumption; and one type of indirect cost: productivity loss due to disability. METHODS: The National Population Health Survey, conducted in all Canadian provinces by Statistics Canada between 1994 and 2011, provides self-reported longitudinal data for body mass index and the frequency of health care utilization and disability. RESULTS: When we compared obese adults in Quebec to those with a normal weight at the beginning of the follow-up period, we observed that the former had significantly more frequent visits to the physician, more frequent hospital stays and higher consumption of drugs between 1994 and 2011. We estimated the annual cost of the excess health care utilization and excess disability at more than CAD $2.9 billion in 2011. CONCLUSION: The results confirm that, similar to what had been found elsewhere in Canada and abroad, there are important economic consequences associated with overweight and obesity in Quebec.